2020
DOI: 10.1021/acs.joc.0c01020
|View full text |Cite
|
Sign up to set email alerts
|

Formal α-Allylation of Primary Amines by a Dearomative, Palladium-Catalyzed Umpolung Allylation of N-(Aryloxy)imines

Abstract: N-(Aryloxy)­imines, readily accessible by condensation/tautomerization of (pseudo)­benzylic primary amines and 2,6-di-tert-butyl-1,4-benzoquinone, undergo efficient allylation to afford a wide range of homoallylic primary amines following hydrolytic workup. Deprotonation of N-(aryloxy)­imines generates a delocalized 2-azaallyl anion-type nucleophile that engages in dearomative C–C bond-forming reactions with allylpalladium­(II) electrophiles generated from allylic tert-butyl carbonates. This reactivity umpolun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 94 publications
2
2
0
Order By: Relevance
“…13 C­{ 1 H} NMR (101 MHz, CDCl 3 ) δ: 162.2 (d, J 1 C‑F = 246.2 Hz), 145.8, 133.6 (d, J 4 C‑F = 3.2 Hz), 131.7, 128.6, 127.6 (d, J 3 C‑F = 7.9 Hz), 127.2, 126.9 (d, J 4 C‑F = 1.9 Hz), 126.4, 115.5 (d, J 2 C‑F = 21.5 Hz), 55.9, 43.5 ppm. The spectroscopic data for this product match the literature data …”
Section: Methodssupporting
confidence: 82%
See 2 more Smart Citations
“…13 C­{ 1 H} NMR (101 MHz, CDCl 3 ) δ: 162.2 (d, J 1 C‑F = 246.2 Hz), 145.8, 133.6 (d, J 4 C‑F = 3.2 Hz), 131.7, 128.6, 127.6 (d, J 3 C‑F = 7.9 Hz), 127.2, 126.9 (d, J 4 C‑F = 1.9 Hz), 126.4, 115.5 (d, J 2 C‑F = 21.5 Hz), 55.9, 43.5 ppm. The spectroscopic data for this product match the literature data …”
Section: Methodssupporting
confidence: 82%
“…13 C­{ 1 H} NMR (101 MHz, CDCl 3 ) δ: 145.8, 135.9, 132.8, 131.7, 128.8, 128.6, 127.9, 127.4, 127.2, 126.4, 55.9, 43.5 ppm. The spectroscopic data for this product match the literature data …”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…Our research group has developed several quinone-catalyzed or quinone-mediated transformations for the synthesis of amine derivatives. During the development of a stepwise umpolung approach for the α-allylation of benzylic amines with allylpalladium species, we observed that iminoquinones derived from 3-butenylamines underwent cyclization by intramolecular C–N bond formation, leading to pyrrole products in low yields (see the Supporting Information). Importantly, control experiments ruled out the intervention of Pd as a catalyst.…”
mentioning
confidence: 99%